Student Worship Obedience Stage in Higher Education - Nuraiman, Nuraiman; Pasaleron, Roni; Hamdi, Hafizul; Zahro, Fatma; Albizar, Albizar (Ahlussunnah: Journal of Islamic Education, 2023)
The level of worship is an achievement that needs to be improved by a servant so that he is more active in carrying out worship. This study aims to describe the extent to which the stages of obedience to worship in college students. This study uses a qualitative method with a case study approach (case study design). Data sources were taken from sixteen informants through in-depth interviews who were selected using a purposive sampling technique. All informants were active female students from various departments at Padang State University in 2020, 2021, and 2022 cohorts students. All interview results were then analyzed thematically using analytical methods. Miles & Huberman data models. The results of the analysis show that there are four levels of worship that female students carry out, namely observance of prayer, fasting, reading the Quran, and giving alms. And the research findings on student worship observances are quite good, such as prayer, fasting, reading the Quran, and giving alms. The results of this study can be used as initial data for future researchers to examine this issue in different contexts and issues.